rozwiaz rownania -(2x-1)=4
2(x+1)=x
2t-(3t+1)=6
-(4+x)=2(3-x)
3(y+6)-y=2(y+9)
(x-7)-2(3x+5)=5
wielkie dzieki
a)-2x+1=4->-2x=3->x=-3/2
b)2x+2=x->2=-x->x=-2
c)2t-3t-1=6->-t=7->t=7
d)-4-x=6-2x->-x=10-2x->x=10
e)3y+18-y=2y+18->2y+18=2y+18->0=0 równanie tożsamościowe
f) x-7-6x-10=5->-5x=22->x=-22/5
a) -(2x-1)=4
-2x+1=4
-2x=3
x=-2/3
b)
2x+2=x
-x=2
x=-2
c)
2t-3t-1=6
-t=7
t=-7
-4-x=6-2x
x=10
d)
3y+18-y=2y+18
y=0
e)(x-7)-2(3x+5)=5
x-7 -6x-10=5
-5x=22
x=-22/5
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
a)-2x+1=4->-2x=3->x=-3/2
b)2x+2=x->2=-x->x=-2
c)2t-3t-1=6->-t=7->t=7
d)-4-x=6-2x->-x=10-2x->x=10
e)3y+18-y=2y+18->2y+18=2y+18->0=0 równanie tożsamościowe
f) x-7-6x-10=5->-5x=22->x=-22/5
a) -(2x-1)=4
-2x+1=4
-2x=3
x=-2/3
b)
2(x+1)=x
2x+2=x
-x=2
x=-2
c)
2t-(3t+1)=6
2t-3t-1=6
-t=7
t=-7
-(4+x)=2(3-x)
-4-x=6-2x
x=10
d)
3(y+6)-y=2(y+9)
3y+18-y=2y+18
y=0
e)(x-7)-2(3x+5)=5
x-7 -6x-10=5
-5x=22
x=-22/5